OPTIMIZATION OF POLICY IMPLEMENTATION MODEL OF SIMPUS KIA (MANAGEMENT INFORMATION SYSTEM IN PUBLIC HEALTH CENTER REGARDING MATERNAL AND CHILD HEALTH) - Machfudloh Machfudloh; Ainul Muthoharoh (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
In the effort to achieve the target of SDG's (Sustainable Development Goals) which is in year 2030 Maternal Mortality Rate (MMR) in Indonesia is expected to reach 70 per 100,000 live births, therefore Public Health Center (Puskesmas) need to improve management of public health service. Puskesmas Management Information System (SIMPUS) can provide easiness, quick, and accuracy in data collection, processing, archiving, and presentation of information and reporting, in order to assist management in decision making area of Maternal and Child Health (KIA) in Puskesmas.Decision making will be easier if all the required information is available. Based on preliminary study conducted in Puskesmas of Demak District, there are 19 (70,37%) Puskesmas which in management information system of puskesmas (SIMPUS KIA) has been done by computerized offline or not yet integrated and (32,63%) done by computerized online or integrated to Demak District Health OfficeThe objective of the research is to explore the management information system of SIMPUS KIA in public health centers of Demak district. This study used descriptive qualitative method. Data collection techniques was in-depth interviews. Population in this research is midwives in Puskesmas which in management information system SIMPUS) KIA has been done by computerized offline.The results of this study are midwives have understanding regarding the definition of SIMPUS, SIMPUS content, SIMPUS goals, SIMPUS benefits, SIMPUS constraints, but there are various reasons why SIMPUS has been done offline, namely lack of human resources, lack of funding and the need for additional new features as it is still very simple in terms of health services record.This research is expected to benefit the community, health workers and educational institutions to strive to improve the quality of health services.